Polygenic risk scores of several subtypes of epilepsies in a founder population. (June 2020) - Moreau, Claudia; Rébillard, Rose-Marie; Wolking, Stefan; Michaud, Jacques; Tremblay, Frédérique; Girard, Alexandre; Bouchard, Joanie; Minassian, Berge; Laprise, Catherine; Cossette, Patrick; Girard, Simon L.
Abstract : Objective: Polygenic risk scores (PRSs) are used to quantify the cumulative effects of a number of genetic variants, which may individually have a very small effect on susceptibility to a disease; we used PRSs to better understand the genetic contribution to common epilepsy and its subtypes. Methods: We first replicated previous single associations using 373 unrelated patients. We then calculated PRSs in the same French Canadian patients with epilepsy divided into 7 epilepsy subtypes and population-based controls. We fitted a logistic mixed model to calculate the variance explained by the PRS using pseudo-R 2 statistics. Results: We show that the PRS explains more of the variance in idiopathic generalized epilepsy than in patients with nonacquired focal epilepsy. We also demonstrate that the variance explained is different within each epilepsy subtype. Conclusions: Globally, we support the notion that PRSs provide a reliable measure to rightfully estimate the contribution of genetic factors to the pathophysiologic mechanism of epilepsies, but further studies are needed on PRSs before they can be used clinically.